Debating the “Science of Reading” and its Impact on Policy - Bartlett, Lesley (2025)
In the past 20 years, the United States has witnessed the emergence of a “science of reading” movement that has fueled new reading legislation in 45 states and the District of Columbia. This article examines debates about and within the “science of reading” and discusses its impact on reading policies across the United States. It highlights concerns generated by the overly narrow focus on phonics and the lack of attention to the broader evidence regarding reading instruction. Studies have shown that the impact of the "science of reading" has had implications that deserve further analysis. Contemporary public policies have reduced the focus of curricula and assessments to phonics. By focusing on phonetic aspects, other facets of reading have been overlooked, such as the use of language in different communicative contexts, the relationship between reading and writing, and student motivation and interest. There is a need for more studies on the "science of teaching reading," as well as attention to the acute shortage of trained teachers and the ways in which a multitude of social inequalities shape children’s opportunities to learn.